Audit Sistem Informasi Akademik Pada Universitas XYZ Menggunakan COBIT 5 Pada Domain MEA - Agung, Halim; Fernandes Andry, Johanes (Institut Teknologi dan Bisnis Kalbis, 2019)
The study was conducted to measure the level of capability of the academic information system towards the achievement of the university’s vision and mission. The researcher examined the impact that occurred on the university regarding the level of capability of the academic information system. The focus of this study is about effectiveness, efficiency, functional information technology units in academic information systems, integrity, saveguarding assets, reliability, confidentiality, availability and security. The researcher conducts literature studies, interviews, distributing questionnaires, examines documents and analyzes the results of questionnaire dissemination and document checking to obtain actual values from the level of capability of academic information systems and factors that affect academic information systems. The researcher processes the statistical data in the form of validity and reliability tests. Researchers use the COBIT 5 framework on 1 domain, namely the Monitor, Evaluate and Assess (MEA) domain to conduct research on the capabilities of academic information systems. The results of the study are in the form of recommendations for solutions for improving the capabilities of academic information systems at universities.